Subclinical hypothyroidism. Issue 3 (March 2019) - Grice, Adam
Subclinical hypothyroidism is a common condition associated with a raised thyroid-stimulating hormone and a normal serum free thyroxine that affects about 10% of females over 55 years in age. The most common cause is autoimmune thyroid disease, with 2.5% of patients with subclinical hypothyroidism progressing to clinically overt hypothyroidism each year. The rate of progression is higher in patients with anti-thyroid peroxidase antibodies and higher levels of thyroid-stimulating hormone. Only a small proportion of patients with subclinical hypothyroidism have symptoms, and although there is some debate in the literature about which patients should be treated, the National Institute for Health and Care Excellence clinical knowledge summaries give clear recommendations. There is an increased risk of cardiovascular disease in patients with subclinical hypothyroidism; it is uncertain whether treatment with levothyroxine reduces this risk. When deciding whether to treat subclinical hypothyroidism consider the patient's age, symptoms, presence of anti-thyroid peroxidase antibodies, thyroid-stimulating hormone levels and risk factors such as cardiovascular disease.